EFFECT OF PRINCIPALS’ ADMINISTRATIVE PRACTICES ON STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN MACHAKOS SUB-COUNTY, MACHAKOS COUNTY, KENYA - TIFFANY NDANU NDUNDA (Machakos University Press, 2025)
The interest in school leadership is based on the belief it can significantly influence directly or indirectly, the teaching and quality of learning in schools, and as a result student achievement. This study investigated the effect of principals’ administrative practices on students’ academic performance in public secondary schools in Machakos sub-County, Machakos County, Kenya. This study was guided by these objectives: to establish the effect of human resource management practices on students’ academic performance; to establish the effect of curriculum implementation practices on students’ academic performance; to determine the effect of students’ welfare practices on students’ academic performance and to examine the effect of financial management practices on students’ academic performance in public secondary schools in Machakos Sub-County, Machakos County, Kenya. The study was based on the human capital theory and prudential theory. Descriptive research design was used for this study. The target population for this study were 48 principals and 400 teachers totalling to 448 respondents from which a sample of 15 principals and 120 teachers were chosen using simple random sampling. Questionnaires were used to collect data from the respondents. Validity was established through expert judgement. The research used Cronbach alpha formula to test reliability. Cronbach’s alpha coefficient of 0.9641 was realized indicating the consistency of research instruments. Data collected were coded and analysed with the help of Statistics and Data (Stata) analysis package. Descriptive statistics in form of mean and standard deviation were used to display the data. Inferential statistics specifically regression analysis was used to show the relationship and strength of the relationships among study variables respectively. The study found that human resource management practices and financial management practices had a positive and statistically significant effect on students’ academic performance. In addition, curriculum implementation practices had a negative and statistically significant effect on students’ academic performance. However, students’ welfare practices did not have a statistically significant effect on students’ academic performance in public secondary schools in Machakos Sub-County, Machakos County. Based on the findings, the study recommends that in the aspect of human resource management practices, there is need for the principal to recognize teachers who have contributed positively to improving the quality of education; principals ought to devise other ways of curriculum implementation practices which motivates the teachers and the students other than monitoring the classroom attendance of the teachers, regular internal assessments in the school, or even emphasizing covering the syllabus on time; and regarding financial management practices there is need for the principal to have a good administrative financial skills, ensure the bursar office provides full accounting reports on time, allow students to continue learning even though they have fee arrears, and ensure all the accounts records are well kept. The study will add to the already available few empirical pieces of literature on principals’ administrative practices and public secondary school academic performance in Kenya and the world.